STATE ISLAM AND OPPOSITIONAL ISLAM: The Rearticulation of Islamic Politics From Jokowi to Prabowo in Indonesia - Ahmad Dawam Pratiknyo (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2026)
This article examines the transformation of Islam-state relations in Indonesia through a comparative analysis of two periods of government: Joko Widodo's second term (2019-2024) and the early presidency of Prabowo Subianto (2024-present). Drawing on qualitative library research and critical discourse analysis, this article proposes the conceptual framework of